Avaliação do Programa Nacional de Assistência Estudantil na Universidade Federal de Alfenas - Barbosa, Alex Trindade (2017)
The National Program of Student Assistance (PNAES) aims to extend the conditions of permanence of speeches in the federal public higher education. The objective of the research of this work is to evaluate the effectiveness of the PNAES to answer a question if the PNAES was a success or failure at the Federal University of Alfenas (UNIFAL-MG), from 2014 to 2016. For this, of relative avoidance and replication index, which compare the proportion of avoidance and disapproval among students not assisted and assisted by the PNAES. The results of the indices are used to evaluate the effectiveness of the PNAES. The evaluation process followed a logical framework structure that details the PNAES in product, activities, objectives and purpose. In addition, it was used as a multiple correspondence analysis technique to analyze other variables linked to students' permanence beyond student assistance. The specific objectives of the research are: 1) to elaborate the relative rejection index and the relative avoidance index, to measure the results of the PNAES; 2) to apply the assessment tool, called the Logical Framework, to guide an evaluation of the effectiveness of the NAPA in UNIFAL-MG; and 3) to analyze other variables possibly associated with the permanence of students in UNIFAL-MG, in addition to the student's actions, such as the non-compulsory internship and research, monitoring and extension activities. An evaluation of the effectiveness of incoming students was carried out in the first and second semesters of 2014. I found that it is not a participant of all courses, since in the semesters the students assisted were evaded in equal or lesser proportion than the unassisted students. With regard to failure, the PNAES was effective in 64% of the courses analyzed in 1/2014 and in approximately 66% of the courses analyzed in 2 / 2014. It was concluded that the PNAES was a success for the period analyzed with However, with a caveat of the courses that need studies to raise the pairs of student disapprovals. The application of the technique of multiple correspondence analysis makes it possible to raise the hypothesis: that as research, monitoring and extension activities are associated to the stay of incoming students in the period between 1º / 2014 until 1º / 2016, an association that can not be applied with for non-compulsory students entering the 1st / 2015 and the 1st / 2016.